Preventing and mitigating AIDS in Sub-Saharan Africa : research and data priorities for the social and behavioral sciences - Cohen, Barney, 1959-; Trussell, James (National Academy Press, 1996)
The AIDS epidemic in Sub-Saharan Africa continues to affect all facets of life throughout the subcontinent. Deaths related to AIDS have driven down the life expectancy rate of residents in Zambia, Kenya, and Uganda with far-reaching implications. This book details the current state of the AIDS epidemic in Africa and what is known about the behaviors that contribute to the transmission of the HIV infection. It lays out what research is needed and what is necessary to design more effective prevention programs.